The State and Marriage: Cut the Connection - Hill, Daniel J. (Tyndale bulletin, 2017)
I argue that the connection between the state and the institution of marriage should be cut. More precisely, I argue that the state should not (I) solemnise or purport to solemnise any marriages, (II) register any marriages and (III) make any laws, civil or criminal, respecting marriage. I advance several arguments for this thesis, and then respond to many possible objections. I do not argue for any change in any of the typical Western laws respecting sexual intercourse; in particular, I do not argue for any change in the laws regarding rape, the age of consent to intercourse or intercourse with a minor.